Efficacy and risks of the use of psychotropics drugs in children and adolescents with depression disorders: a literature review (Research, Society and Development, 2022)
The transition from childhood to adolescence is a period of life characterized by hormonal and physiological changes. In this phase, there are also several social interactions that change according to the environment, imposing responsibilities and a desire for new cycles. These demands make people vulnerable and insecure to certain feelings, generating mood disorders that can progress to major depression disorder. Objective: to evaluate the efficacy and risks of psychotropic drugs prescribed to children and adolescents with depression disorders. Method: This is a bibliographic review of scientific articles of the descriptive-quantitative type, searched online, on Google Scholar platforms, Virtual Health Library - VHL (Medline, IBECS, LILACS), Portal Periodicals CAPES and SciELO and prepared from 1987 to 2021. The search used the descriptors, antidepressants, psychotropic drugs, adverse effects, depressed children and adolescents, in Portuguese, English and Spanish. Result: the same psychotropic drug is used in several other mental disorders, such as bipolar disorder and anxiety. Drugs that demonstrated significant efficacy were Serotonin Reuptake Inhibitors (SSRIs) such as paroxetine, sertraline and fluoxetine. Final Considerations: the psychotropic drugs used to treat depression in children and adolescents, although they are effective in some cases, nevertheless cause several adverse effects. The use of these drugs should not be carried out indiscriminately so that their risks do not outweigh their benefits, and it is essential to assess the causes of childhood depression and the clinical follow-up of patients by a multidisciplinary team.